Challenges and Strategies for Educating Medical Students During the COVID-19 Pandemic: A Systematic Review - Khalil Kalavani; Saber Azami-Aghdash; Zahra Zare; Elham Shami; Mahdiyeh Heydari (Gazi Medical Journal)
During the coronavirus disease-2019 (COVID-19) pandemic, medical student education faced many challenges as these students became involved in the treatment of disease. Therefore, the purpose of this study was to systematically review the challenges and strategies for medical student education during the COVID-19 pandemic. This study is a systematic review. To find the necessary documents and collect the information, Web of Science, PubMed, Scopus, and Embase databases, websites for relevant journals, and search engines such as Google Scholar, were used from January 2019 to the end of 2022. The data were analyzed using content analysis and descriptive statistics. Of the 14,474 studies found, 82 documents were ultimately included. Most studies were conducted in the United States (18%), and the largest target population was U.S. residents (41%). A total of 228 challenges were identified and categorized into seven major themes (financial constraints and infrastructure development, international education, assessment and testing system, student health and preparation, professional ethics, faculty empowerment, and virtual education) and 14 subthemes. The most significant challenges were virtual education, student health, and financial and infrastructure constraints. Solutions were also categorized into five main areas: virtual education, infrastructure and physical environment, educational approach, faculty empowerment, and health, along with 23 subcategories. Identifying and analyzing the challenges presented in this study and the solutions offered could help policymakers and higher education managers make evidence-based decisions tailored to local conditions, and turn the COVID-19 crisis into an educational opportunity.